2017
DOI: 10.1186/s13054-017-1600-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low tidal ventilation on lung strain correlate with respiratory system compliance

Abstract: BackgroundThe effect of alterations in tidal volume on mortality of acute respiratory distress syndrome (ARDS) is determined by respiratory system compliance. We aimed to investigate the effects of different tidal volumes on lung strain in ARDS patients who had various levels of respiratory system compliance.MethodsNineteen patients were divided into high (Chigh group) and low (Clow group) respiratory system compliance groups based on their respiratory system compliance values. We defined compliance ≥0.6 ml/(c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
2
13
0
1
Order By: Relevance
“…In 2015, Amato and colleagues [12] presented the results of a retrospective analysis of individual patient data, with the conclusion that the driving pressure (tidal volume normalized to lung compliance) was better associated to survival in ARDS patients than either tidal volume or plateau pressure separately. Following this, various studies have corroborated those results [13, 35], and shown that driving pressure was a good indicator of lung stress [36], higher driving pressures were associated with more postoperative pulmonary complications [35], and higher driving pressures may induce lung injury more easily in patients with low respiratory system compliance [37]. The results in this paper support the hypothesis that higher driving pressure results in increases in several important indices of VILI.…”
Section: Discussionsupporting
confidence: 83%
“…In 2015, Amato and colleagues [12] presented the results of a retrospective analysis of individual patient data, with the conclusion that the driving pressure (tidal volume normalized to lung compliance) was better associated to survival in ARDS patients than either tidal volume or plateau pressure separately. Following this, various studies have corroborated those results [13, 35], and shown that driving pressure was a good indicator of lung stress [36], higher driving pressures were associated with more postoperative pulmonary complications [35], and higher driving pressures may induce lung injury more easily in patients with low respiratory system compliance [37]. The results in this paper support the hypothesis that higher driving pressure results in increases in several important indices of VILI.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, the use of low V T leads to a significant increase in static C RS without affecting the linear compliance measured between lower and upper inflection point. Lung volume, as defined by Rec, did not change nor patients' position varied among the study steps, and chest wall elastance was likely constant over the entire course of the study, thus suggesting that any observed change in respiratory mechanics reflects variations in lung mechanics: In particular, the results inhering static and quasi-static compliance indicate some degree of lung overdistention when higher V T were used, as already suggested by other authors [20,49,50].…”
Section: Discussionsupporting
confidence: 62%
“…More importantly, the compliance and functional residual capacity of the baby lung are proportional (23), and VILI is related to its excessive stress and strain. To prevent VILI, we must limit VT based on the functional residual capacity of the baby's lungs rather than the ideal weight (24)(25)(26). Recently, Amato et al reported that the Crs-standardized VT was a better predictor of prognosis in patients with ARDS than VT alone.…”
Section: Development Of Driving Pressurementioning
confidence: 99%